Effect of Cu and Fe Metals on the Synthesis of Activated Carbon Composites of MOFs Cu(TAC) and Fe(TAC) - Anggi Nurhasanah Siregar; Jasmidi; Moondra Zubir; Rini Selly; Putri Faradilla (Universitas Negeri Medan, 2025)
The research focuses on improving the structure and quality of activated carbon by synthesizing porous polymers or Metal-Organic Frameworks (MOFs). Characterization of AC-Cu(TAC)2 and AC-Fe(TAC)3 is carried out using XRD, SEM, and EDX instruments. Characterization of AC- Cu(TAC)2 and AC-Fe(TAC)2 revealed that the observed XRD pattern is representative of the structure of crystalline materials, with AC-Cu(TAC)2 and AC-Fe(TAC)3 having a crystallinity of 40% with both materials forming a triclinic crystal system. Characterization based on SEM at 200x magnification shows that the fibers are interbonded and attached to the cross-section on AC- Cu(TAC)2 , having a relatively large porosity so that it shows a fairly strong bond between activated carbon and Cu(TAC) MOFs. the size of the fragmented fiber particles in AC-Fe(TAC)3 which is relatively not the same as the smaller porosity. EDX characterization shows that Cu and Fe metals are one of the composite materials.